The Shield of Traditionalism: A Critical Analysis of Technological Alienation and the Romanticism of Local Education - Bari, Fathul; Acetylena, Sita; Husni, Muhammad (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2026)
The phenomenon of reviving traditional education has emerged as a reaction to the rapid development of science and technology (S&T), which is often perceived as a foreign threat. This study aims to uncover the motives behind the resurgence of traditionalism and analyze its impact on the global competitiveness of local communities. Adopting a qualitative approach with critical discourse analysis, the research examines local wisdom-based education policies and the public narratives of policymakers. Data were collected through a literature study, contrasting the concept of modernity with the theory of alienation to observe shifting value patterns. The discussion reveals that the tendency to worship local romanticism often functions as a sociological defense mechanism. Technologically illiterate communities tend to seek refuge in "authentic" yet static values as a spiritual consolation for lagging behind developed nations. The findings indicate that reviving traditional values without integrating modern technology creates a sense of false satisfaction. This causes communities to become trapped in a romanticism of the past, hindering adaptation to sophisticated foreign technological models. Consequently, this reliance on rigid traditionalism widens the developmental gap and diminishes local competitiveness in the era of globalization.